IMPLEMENTASI FUZZY LOGIC CONTROLLER PADA ALAT PENGONTROL PH AIR AKUARIUM AKUAPONIK MENGGUNAKAN VOLUME LARUTAN PH UP DAN PH DOWN DENGAN METODE MAMDANI - I Dewa Gde Panji Adyatma; Bambang Siswojo; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
Aquaponics is a system of cultivating fish (aquaculture) and plants (hydroponics) together in a circulated/mutually beneficial ecosystem that uses natural bacteria to convert fish feed waste & residues into plant nutrients. Aquaponics aquaculture innovation is considered to play an important role in meeting the needs of fish and vegetables in the market. In addition to being economical, the potential of aquaponics cultivation can be a reserve for fish and vegetable needs in waters and rice fields. Water quality is a key parameter in aquaponics. To get optimal results, water conditions must be maintained, one of which is the pH of the water. The degree of acidity of the growing media and the sangan water affects the growth of fish and plants in aquaponics. If the pH level is too low or too high, it can interfere with the growth of fish and plants. The implementation of the fuzzy logic control method mamdani on controlling the pH of the water is a way to maintain the quality of the water in the aquarium, especially the pH so that the growth of fish and plants is optimal. Controlling the pH of water in aquaponics using the mamdani fuzzy logic method, by determining the membership function so that it can control the volume output of the pH up solution or pH down solution so that the pH of the water in aquaponics remains neutral. From the results of the study, the tool was able to control the pH of water in aquaponics in accordance with the desired membership function setpoint, namely 6.5 -7 with an average error of 0.14% regulating the output of the pH up and pH down solution volumes with the desired value. Keywords: Aquaponics, pH, Fuzzy logic Mamdani, pH up solution, pH down solution